PERENCANAAN PANTI JOMPO DENGAN PENEKANAN ARSITEKTUR TROPIS DI KOTA SAMARINDA - Nirwanda, Andik; Dovianto, Rusdi; Mudrajad, Dimas Bintang (Jurnal Totem : Architecture, Environment, Region and Local Wisdom, 2020)
Nursing Home is a social institution that has the responsibility to provide social services and the need for elderly life. The city of Samarinda still lacks nursing home as a container for them to stay, nursing home is planned to receive elderly ministry with age 60 years and above in accordance with the LAW. 13 year 2018 about elderly welfare. In planning this nursing home through several stages such as the method of data collection after obtained further processed through an approach that corresponds to the scope of analysis and then the resolution decisions that have been analyzed this Is poured in the form of design concept to be applied. After that, the plan analysis of nursing home is detailed such as to pay attention to several stages such as space and activity needs, KDB AND KDH analysis, site analysis, analysis of form and materials, structure analysis, and building utilitiesÂ  Formed arrangement towards the concept of planning nursing home. The concept of planning is done by the approach of tropical architecture concept that will be applied to the nursing home building, the entire building that will be planned in the nursing home will follow the rules of the concept of tropical architecture. Nursing Home with emphasis This tropical architecture is hoped to be a problem solver for the lack of nursing homes in the city of Samarinda. Â Keywords: Nursing home, Samarinda City, Tropical conceptÂ